Identification of an Intestinal Neutral Glycosphingolipid as a Phenotype-Specific Receptor for the K88ad Fimbrial Adhesin of Escherichia coli - Grange, Philippe A. (American Society for Microbiology, 1999)
In this study, we identified a receptor for the K88ad fimbrial adhesin of Escherichia coli in neutral glycosphingolipid preparations from intestinal epithelial cells of K88ad-adhesive pigs, which was absent in preparations from K88ad-nonadhesive pigs. Neither K88ab nor K88ac adhesin variants bound to this neutral glycosphingolipid. Because this receptor is an intestinal glycosphingolipid that binds K88ad adhesin, it has been designated IGLad. Carbohydrate compositional analysis of a partially purified preparation of IGLad identified galactose, glucose, and N-acetylglucosamine in a ratio of 1.5:1.0:0.5 as the major monosaccharides. Preliminary characterization experiments using lectins showed that IGLad contains the terminal glycanic structure Galβ1-4GlcNAc. Removal of terminal β-linked galactose residues from IGLad decreased the recognition of IGLad by the K88ad adhesin, indicating that terminal β-linked galactose is an essential component of the K88ad adhesin recognition site on IGLad. Studies with purified glycosphingolipid standards demonstrated that K88ad adhesin binds to neolactotetraosylceramide (nLc(4)Cer) (Galβ1-4GlcNAcβ1-3Galβ1-4Glcβ1-1Cer), lactotriosylceramide (GlcNAcβ1-3Galβ1-4Glcβ1-1Cer) and lactotetraosylceramide (Galβ1-3GlcNAcβ1-3Galβ1-4Glcβ1-1Cer). Based on these studies, IGLad appears to be nLc(4)Cer.